The use of peganum harmala in medicine - Ravshanbek qizi, O'rmonjonova Dilnavoz; Murodjon qizi, Iqboldinova Mohiraxon (American Journal of Biomedicine and Pharmacy, 2025)
Peganum harmala, commonly known as wild rue or isiriq, is a traditional medicinal plant widely used in Central Asia, the Middle East, and parts of Europe. It contains biologically active alkaloids such as harmine, harmaline, and harmalol, which exhibit antimicrobial, anti-inflammatory, analgesic, antiparasitic, and neurological effects. In Uzbekistan, Peganum harmala has been used in folk medicine for centuries for treating respiratory diseases, digestive disorders, nervous system problems, and spiritual-healing rituals. Modern scientific research also confirms its pharmacological potential, although its toxicity requires careful and controlled use. Medicinal plants play a vital role in traditional and modern healthcare systems across the world. Peganum harmala, known as wild rue or isiriq, is considered one of the most important traditional medicinal plants due to its strong biological activity and wide cultural significance. Historically, it has been used for respiratory infections, digestive problems, nervous disorders, menstrual pain, and skin diseases. Additionally, it is culturally associated with protective rituals against illness and negative energy in many Central Asian societies This article reviews its medicinal importance, traditional applications, pharmacological properties, and relevance in the Uzbek context.